Competencies for nursing in a digital world. Methodology, results, and use of the DACH-recommendations for nursing informatics core competency areas in Austria, Germany, and Switzerland. (2nd October 2019) - Egbert, Nicole; Thye, Johannes; Hackl, Werner O.; Müller-Staub, Maria; Ammenwerth, Elske; Hübner, Ursula
ABSTRACT: While Nursing Informatics competencies seem essential for the daily work of nurses, they are not formally integrated into nursing education in Austria, Germany and Switzerland, nor are there any national educational recommendations. The aim of this paper is to show how such recommendations can be developed, what competency areas are most relevant in the three countries and how the recommendations can be implemented in practice. To this end, a triple iterative procedure was proposed and applied starting with national health informatics recommendations for other professionals, matching and enriching these findings with topics from the international literature and finally validating them in an expert survey with 87 experts and in focus group sessions. Out of the 24 compiled competency areas, the relevance ratings of the following four recommended areas achieved values above 90%: nursing documentation (including terminologies), principles of nursing informatics, data protection and security, and quality assurance and quality management. As there were no significant differences between the three countries, these findings laid the foundation of the DACH Recommendations of Nursing Informatics as joint German (D), Austrian (A), and Swiss (CH) recommendations in Nursing Informatics. The methodology proposed has been utilized internationally, which demonstrates the added value of this study also outside the confines of Austria, Germany, Switzerland.